Regulation of Fungal Infection by a Combination of Amphotericin B and Peptide 2, a Lactoferrin Peptide That Activates Neutrophils - Okamoto, Tetsuro (American Society for Microbiology, 2004)
To establish a novel strategy for the control of fungal infection, we examined the antifungal and neutrophil-activating activities of antimicrobial peptides. The duration of survival of 50% of mice injected with a lethal dose of Candida albicans (5 × 10(8) cells) or Aspergillus fumigatus (1 × 10(8) cells) was prolonged 3 to 5 days by the injection of 10 μg of peptide 2 (a lactoferrin peptide) and 10 μg of α-defensin 1 for five consecutive days and was prolonged 5 to 13 days by the injection of 0.1 μg of granulocyte-monocyte colony-stimulating factor (GM-CSF) and 0.5 μg of amphotericin B. When mice received a combined injection of peptide 2 (10 μg/day) with amphotericin B (0.5 μg/day) for 5 days after the lethal fungal inoculation, their survival was greatly prolonged and some mice continued to live for more than 5 weeks, although the effective doses of peptide 2 for 50 and 100% suppression of Candida or Aspergillus colony formation were about one-third and one-half those of amphotericin B, respectively. In vitro, peptide 2 as well as GM-CSF increased the Candida and Aspergillus killing activities of neutrophils, but peptides such as α-defensin 1, β-defensin 2, and histatin 5 did not upregulate the killing activity. GM-CSF together with peptide 2 but not other peptides enhanced the production of superoxide (O(2)(−)) by neutrophils. The upregulation by peptide 2 was confirmed by the activation of the O(2)(−)-generating pathway, i.e., activation of large-molecule guanine binding protein, phosphatidyl-inositol 3-kinase, protein kinase C, and p47(phox) as well as p67(phox). In conclusion, different from natural antimicrobial peptides, peptide 2 has a potent neutrophil-activating effect which could be advantageous for its clinical use in combination with antifungal drugs.